The 2018 Japan Floods Increased the Frequency of Yokukansan Prescriptions Among Elderly: A Retrospective Cohort Study - Ishida, Ryoko; Yoshida, Shuhei; Kashima, Saori; Okazaki, Yuji; Matsumoto, Masatoshi (Frontiers in Nutrition, 2022)
Objective: The impact of the 2018 Japan Floods on prescriptions of Yokukansan was evaluated. Methods: This was a retrospective cohort study based on the National Database of Health Insurance Claims which covers all the prescriptions issued in Japan. Participants were patients aged 65 or older who received any medical care at medical institutions located in the three most-severely affected prefectures between one year before and after the disaster. We analyzed the number of new prescriptions of Yokukansan and other Kampo drugs among those who had not been prescribed any Kampo for one year before the disaster. Kaplan-Meier analysis and a Cox proportional hazards model were used to evaluate the risk of the disaster for a new prescription. Results: Subjects comprised 1,372,417 people (including 12,787 victims, 0.93%). The hazard ratio (HR) of the disaster for Yokukansan prescriptions was 1.49 (95% confidence intervals (CI): 1.25-1.78), and 1.54 (95% CI: 1.29-1.84) in the crude and age-sex adjusted model, respectively. The HR of the disaster for prescription of other Kampo drugs in the crude and adjusted model was 1.33 (95% CI: 1.27-1.39), and 1.32 (95% CI: 1.27-1.38), respectively. The magnitude of increase of victims prescribed Yokukansan (31.4%) was statistically higher than for those prescribed other Kampo drugs (19.3%) (p<0.001). Conclusion: The disaster increased prescriptions of both Yokukansan and other Kampo drugs among elderly victims. The increase was more remarkable in Yokukansan than other Kampo drugs. Clinicians and policymakers should be aware of the increased need for Yokukansan in times of natural disaster.